2006
DOI: 10.1049/ip-its:20055014
|View full text |Cite
|
Sign up to set email alerts
|

Roadway traffic monitoring from an unmanned aerial vehicle

Abstract: Roadway networks span large distances and can be difficult to monitor. Most efforts to collect roadway usage data either require a large fixed infrastructure or are labor intensive. Technological advances in electronics and communication have recently enabled an alternative, Unmanned Aerial Vehicles (UAVs). UAVs capable of carrying sensors and communications hardware to relay data to the ground are becoming available on the commercial market. UAVs can cover large areas and focus resources. They can travel at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
71
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(82 citation statements)
references
References 4 publications
0
71
0
3
Order By: Relevance
“…Unmanned aerial vehicles (UAVs) hold promise of great value for transportation research, particularly for traffic data collection (e.g., [1][2][3][4][5]). UAVs have many advantages over ground based traffic sensors [2]: great maneuverability and mobility, wide field of view, and zero impact on ground traffic.…”
Section: Introductionmentioning
confidence: 99%
“…Unmanned aerial vehicles (UAVs) hold promise of great value for transportation research, particularly for traffic data collection (e.g., [1][2][3][4][5]). UAVs have many advantages over ground based traffic sensors [2]: great maneuverability and mobility, wide field of view, and zero impact on ground traffic.…”
Section: Introductionmentioning
confidence: 99%
“…A pulse-coupled neural filter was used to remove background noise before applying the Hough transform. Coifman et al [7] investigated the use of UASs to monitor roadway traffic to facilitate offline planning and real-time management applications. A feasibility study by Ro et al [8], which conducted a field experiment at a local interstate using UASs, concluded that UAS applications will become popular in the transportation area in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…The vehicle detection can be used mostly in the automation of monitoring of traffic and large parking lots. Works about the automatic vehicle recognition have long been published, for example (Coifman, 2006).…”
Section: Introductionmentioning
confidence: 99%